Analyzing the Impact of the Number of Followers and Social Media Advertising Budget on MSME Sales Volume - Sudirjo, Frans; Abu Muna Almaududi Ausat; M Indre Wanof; Hizbul Khootimah Azzaakiyyah; Muhammad Aqib Shafiq (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
Faced with the escalating pressures of digital transformation, Micro, Small, and Medium Enterprises (MSMEs) are struggling to adapt to evolving consumer behavior and intensifying online competition. This study examines the impact of social media engagement—specifically the number of followers and the allocation of advertising budgets—on the sales performance of MSMEs. Employing the Digital Marketing Theory, which emphasizes the strategic importance of online visibility and digital consumer interaction, this research adopts a quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Data were collected through an online survey of 100 MSMEs from various sectors in Semarang, Indonesia. The findings reveal that both the number of social media followers and the advertising budget have a positive and significant influence on the sales volume of MSMEs. A growing follower base indicates increased brand awareness and trust, which in turn enhances the effectiveness of promotional messages and drives purchasing decisions. Additionally, higher engagement levels between consumers and brands on social media platforms are shown to strengthen customer relationships and contribute to higher sales conversion rates. These insights underline the importance of strategic digital marketing efforts for MSMEs aiming to compete effectively in the evolving digital marketplace.